Revisão sistemática dos Pyrgomorphidae sul-americanos (Orthoptera, Acridoidea) - Santos, Claudia Maria Alves dos (2004)
The Pyrgomorphidae of South América are represented by four species, Omura congrua Walker, 1870, Algete brunneri Bolívar, 1905. Deraspiella volxemi (Bolívar, 1884) and Minorissa pustulata Walker, 1870. ln this work, the systematic revision of the species is proposed based on the external morphology, male and female genitalia. Redescriptions of the genera and species and description of D. volxemi's male are included. The validity of the tribe Omurini is confirmed based on the study of the phallic complex, D. volxemi is transferred to another genus and two morphological patterns to D. volxemi are registered. Illustrations of the head, thorax, femur, terminal abdominal segments and genitalia of males and females are given as well as a map showing the geographical distribution of the species.